AI Literacy Research: Frontier for High-Impact Research and Ethics - Ricardo Limongi; Carla Bonato Marcolin (BAR: Brazilian Administration Review)
Artificial intelligence (AI) has emerged as a driving force in scientific development, influencing areas such as Administration and Public Administration, which are central themes of the publication of the Brazilian Administration Review (BAR). Despite transformative promises, AI’s appropriate and ethical use in academia still presents substantial challenges, especially for researchers who require specific skills to understand, critique, and utilize these technologies (Dwivedi et al., 2023; Susarla et al., 2023). Even though it is an important support tool to improve texts, the risks of hallucination (generating wrong information) and transformation of already written texts (plagiarism) worry the academic community. In addition, the continuous advancement of generative language models (LLMs) makes AI-written text detection tools often unreliable. AI literacy emerges, in this context, as an essential competence for researchers to deal with AI tools critically, ethically, and effectively.